Effects of disposable plastics and wooden chopsticks on the anaerobic digestion of food waste. (September 2018) - Lim, Jun Wei; Ting, Daphne Wan Qing; Loh, Kai-Chee; Ge, Tianshu; Tong, Yen Wah
Graphical abstract: Highlights: Batch study on effects of disposable plastics on food waste digestion. PS and PP inhibited biogas production from food waste more than HDPE and WC. Increased surface area of plastics led to greater reduction in methane yield. Reduced contact of microbes and food waste lowered methane production. No obvious changes to microbial consortia of food waste with or without plastics. Abstract: A common challenge for the anaerobic digestion (AD) of food waste (FW) is the contamination by disposable plastic materials and utensils. The objective of this batch study was to investigate the effects of disposable plastic materials – polystyrene (PS), polypropylene (PP), high density polyethylene (HDPE) and wooden chopsticks (WC) on the AD of FW. Results showed that methane production from the AD of FW was inhibited to different extents when different materials were present in FW. PS and PP were found to reduce methane production from food waste more than HDPE and WC. The reduction in methane production was hypothesized to be due to the production of toxic plastic by-products or due to reduced contact between microbes and FW. Pyrosequencing and Field Emission Scanning Electron Microscope (FESEM) results indicated that the reduction in methane production was more likely due to the interference of good contact necessary between microbes and FW for biodegradation, and that the biological processes of AD were not affected by the contamination of plastics. Greater reductions in methane yields were also observed when the surface areas of the disposable materials were increased. Studying the effects of disposable materials on the AD of FW would provide plant operators with more information that could optimise the process of resource recovery from food waste.